The Abilities of Four Species of Nigerian Aquatic Phycomycetes to Utilize Petroleum and Petroleum Products as Sole Carbon Sources - C.E., Odu; C.I.C., Ogbonna; D., Bukbuk; O.O.C., Chukwu; I., Yerima; D., Mustapha (European Scientific Journal, ESJ, 2018)
Studies were carried out on the abilities of four aquatic phycomycetes species isolated from crude oil polluted marine , brackish and fresh water environments in Nigeria to utilize refined Petroleum and Petroleum products as sole sources of carbon. The said species of fungi included Brevilegnia indica, Protoachyla paradoxa, Saprolegnia bhargavi and Thraustotheca clavata. They were grown on fungal culture media which contained mineral salts solution, refined petroleum, kerosene and diesel as sole sources of carbon and agar as a solidifying agent. Two concentrations of each of the resulting oil agar media were used vis 1% and 2%. The resultant medium was then used to culture each of the test fungi in triplicates. The resultant culture plates were then incubated at 25 OC and left for daily observation. The test fungi that grew on each medium were observed for their abilities to emulsify the refined petroleum or its products (diesel and kerosene). Control experiments were also set up using Malt Extract Agar medium. Brevilegnia indica grew on 1% petroleum and diesel growth media but did not grow on kerosene medium. Protoachyla paradoxa grew minimally on diesel medium at 1% and 2% compositions. Saprolegnia bhargavi did not grow on the petroleum agar medium or petroleum products media. Thraustotheca clavata grew minimally on the kerosene medium at both 1% and 2% compositions. The four test fungi emulsified the diesel agar medium at both 1% and 2% compositions. Brevilegnia indica emulsified only petrol at 1% while Non of the isolates emulsified the kerosene medium at both 1% and 2% compositions. Oil globules were also observed in the vegetative hyphae of the test fungi which grew on the experimental culture media. This means that such fungi either degraded or accumulated the petrol or petroleum products in their systems.